Administrative and legal regulation of E-government in the economic activity sphere - Bevz, Svitlana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
The article is devoted to the identify issues that need administrative and legal  regulation in the context of the introduction of e-government in the economic activity sphere. Defining the main tasks for ensuring the development of e-government in the basic sectors of Ukraine, the economy, economic policy or industry is not at all isolated and not specified is established in the article. Whereas the introduction of such a form of state governance in the economic activity sphere entails the establishment of their, separately defined, tasks, which is conditioned by the specific gravity of administrative and legal relations with the participation of economic entities in the implementation of e-government.It has been established that the functioning of the subjects of power authorities in the process of deregulation of economic activity should be aimed at the realization, first of all, of the economic function of the state and be carried out systematically - with the performance of all state governance functions. Implementationofe-government should covered all of the last. This will be facilitated by the proper administrative and legal support for the implementation of e-government tasks in a particular area.The author notes that the digital economy and e-government envisage a digital transformation of requirements enshrined in the legislative framework for the administrative and legal regulation of relevant relations. Before carrying out such activity, it is necessary to create appropriate content relevant mechanism of administrative and legal regulation of state governance in the economic activity sphere. It is can take electronic forms. The article also highlights some features of such a mechanism.The administrative and legal regulation of e-government in the economic activity sphere on a digital economy should ensure the solution of the tasks of implementation of e-government in the relevant sphere, information security, protection of the rights and legitimate interests of economic entities and consumers; monitoring the implementation of business activities and stimulating the introduction of information and communication technologies in the activities of economic entities and subjects of power authorities.